2022
DOI: 10.1111/rssa.12960
|View full text |Cite
|
Sign up to set email alerts
|

Pictures Instead of Survey Questions: An Experimental Investigation of the Feasibility of Using Pictures in a Housing Survey

Abstract: Anyone with a smartphone can take pictures anytime anywhere. This opens the opportunity for researchers to collect photos to augment traditional Web survey data. We conducted an experimental survey asking 2700 members of the Dutch LISS panel about their dwelling conditions. Depending on the condition, they were asked to either take several photos of their house or answer a set of survey questions about the same topics. This paper documents the feasibility of collecting pictures instead of answers in a web surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…In a lab-based study, Baumgartner et al (2022) found that 45% of participants, after extensive training, uploaded valid video recordings of their mobile usage for a seven-day period. While specific data on the compliance rates of enhanced recall in the context of mobile and app usage data donations is lacking, Ilic et al (2022) reported a compliance rate of 64.4% for a similar task related to home heating systems.…”
Section: The Challenges Of Measuring Mobile and App Usage Through Dat...mentioning
confidence: 99%
“…In a lab-based study, Baumgartner et al (2022) found that 45% of participants, after extensive training, uploaded valid video recordings of their mobile usage for a seven-day period. While specific data on the compliance rates of enhanced recall in the context of mobile and app usage data donations is lacking, Ilic et al (2022) reported a compliance rate of 64.4% for a similar task related to home heating systems.…”
Section: The Challenges Of Measuring Mobile and App Usage Through Dat...mentioning
confidence: 99%
“…The participation rates range from 10% in the study by Jäckle et al (2019) asking for photos of receipts, to 55% in the study by Bosch et al (2019a) when asking for a photo of the place where respondents are when answering the survey. Moreover, greater item nonresponse has been found when respondents had to answer by sharing images than when using conventional response formats ( Bosch et al , 2022 ; Ilic et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding preferences, to the best of our knowledge, there is only one survey proposing participants to choose in advance between only images or only conventional ways of answering ( Ilic et al , 2022 ): they found that more than half (57%) of their sample chose images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation